Eating Habits, Energy Density, and Protein Intake Associated with Young Women's Nutritional Status at SMAN 6 Kabupaten Tangerang - Vidyarini, Andra; Razhiddiani, Lathifa Aisyah (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2026)
Adolescence is a critical period of growth characterized by increased energy and balanced nutrient requirements. Nutritional imbalance among adolescent girls may lead to nutritional status problems, such as underweight and overweight, and may contribute to various health issues, including menstrual cycle disorders. Therefore, it is important to understand the factors associated with nutritional status, including eating habits and the energy and protein density of dietary intake. This study aimed to identify the characteristics of respondents, eating habits, energy density, protein density, and nutritional status, as well as to analyze the relationships between eating habits, energy density, protein density, and the nutritional status of adolescent girls at SMAN 6 Tangerang Regency. This study employed a cross-sectional design with a proportional stratified random sampling technique. A total of 86 female students participated in the study. Data were collected through anthropometric measurements to determine nutritional status, questionnaires assessing eating habits, and 2×24-hour food recall interviews. Data analysis was conducted using the Chi-square test to examine the relationship between eating habits and nutritional status, while Spearman correlation analysis was used to assess the relationships between energy density, protein density, and nutritional status. The results showed that the majority of respondents were in the middle adolescence age group (15–17 years). Most participants had normal nutritional status (60.5%), while 26.7% were overweight and 12.8% were underweight. The majority of respondents exhibited poor eating habits, with high dietary energy density and adequate dietary protein density. Statistical analysis revealed significant associations between eating habits and nutritional status, as well as between dietary energy density and nutritional status. In contrast, protein density was not significantly associated with nutritional status. These findings indicate that eating habits and dietary energy quality play important roles in determining the nutritional status of adolescent girls. Therefore, strengthening nutrition education and promoting healthy eating behaviors are essential to support optimal nutritional status among adolescents.